Introduction of the Carotenoid Biosynthesis α-Branch Into Synechocystis sp. PCC 6803 for Lutein Production - Lehmann, Martin; Vamvaka, Evgenia; Torrado, Alejandro; Jahns, Peter; Dann, Marcel; Rosenhammer, Lea; Aziba, Amel; Leister, Dario; Rühle, Thilo (Frontiers in Plant Science, 2021)
Lutein, made by the α-branch of the methyl-erythritol phosphate (MEP) pathway, is one of the most abundant xanthophylls in plants. It is involved in the structural stabilization of light-harvesting complexes, transfer of excitation energy to chlorophylls and photoprotection. In contrast, lutein and the α-branch of the MEP pathway are not present in cyanobacteria. In this study, we genetically engineered the cyanobacterium Synechocystis for the missing MEP α-branch resulting in lutein accumulation. A cassette comprising four Arabidopsis thaliana genes coding for two lycopene cyclases (AtLCYe, AtLCYb) and two hydroxylases (AtCYP97A, AtCYP97C) was introduced into a Synechocystis strain that lacks the endogenous, cyanobacterial lycopene cyclase cruA. The resulting synlut strain showed wild-type growth and only moderate changes in total pigment composition under mixotrophic conditions, indicating that the cruA deficiency can be complemented by Arabidopsis lycopene cyclases leaving the endogenous β-branch intact. A combination of liquid chromatography, UV-Vis detection and mass spectrometry confirmed a low but distinct synthesis of lutein at rates of 4.8 ± 1.5 nmol per litre culture at OD730 (1.03 ± 0.47 mmol mol-1 chlorophyll). In conclusion, synlut provides a suitable platform to study the α-branch of the plastidic MEP pathway and other functions related to lutein in a cyanobacterial host system.